Optimization of delay at intersection in anticipate stuck on the traffic by using software SIDRA intersection 8.0 (Case study : BPKP’s intersection at Banda Aceh) - Rezqi Malia; Raina P. Dinda; Alvisyahri Alvisyahri; Chaira Chaira (Institut Teknologi Sepuluh Nopember (ITS), 2023)
BPKP’s Intersection at Banda Aceh is one of the signalized intersections with four approaches. So there are 16 crossings, 8 diverging, and 8 merging, between vehicles such as delay and congestion. The research uses the program SIDRA Intersection 8.0 to analyze the intersection in its current state and to remodel it. Software The user can select a preset minimum capacity for each little movement in SIDRA Intersection 8.0 (analytical model). The information was gathered from the institute utilizing a video taken using CCTV in the research area. The data from a video included vehicle volume, distances (upstream, downstream, and negotiation) and travel time. In existing condition. The total demand flow is 1060 pcu/h. Approach delay 96.8 sec and level of service is F. The redesign geometry is changed to the roundabout which is assumed as multiple unsignalized junction. The total demand flow in redesign condition at BPKP’s Intersection at Banda Aceh is 1060 pcu/h. Approach delay 3.8 sec and level of service is A.